Daya Saing dan Faktor Determinan Usahatani Kedelai di Lahan Sawah - Krisdiana, Ruly (Jurnal Penelitian Pertanian Tanaman Pangan, 2012)
The objective of the study was to identify competitive advantages and determinant factors for soybean farming in wetland. Research was conducted during the 2010 cropping season in Banyuwangi and Pasuruan Regencies (East Java) and in Demak and Wonogiri Regencies (Central Java) using the survey method. One hundred and twenty eight respondents representing food crop farmers were sampled randomly, including soybean, maize, groundnut, and mungbeans farmers. Results of the study showed that in general the competitive advantage of soybean was lower than that of maize, groundnut, and mungbean. However, in East Java, soybean had higher competitive advantage than groundnut. When the soybean productivity reached 2.183 t/ha with soybean price Rp 5,558/kg in East Java, and soybean productivity 1.672 t/ha with price Rp 5,191/kg in Central Java, soybean crop gave a higher competitive advantage over the other food crops. Similarly, when the soybean price increased to Rp 7,441/kg with soybean productivity of 1,631 t/ha in East Java, or to Rp 7,029/kg with productivity of 1,235 t/ha in Central Java, soybean had a better competitive advantage over the other crops. Soybean farming in East Java was more profitable than that in Central Java. Soybean production cost per unit in East Java was Rp 775/kg with a benefit Rp 3,644/kg and an R/C ratio of 3.19, while the production cost in Central Java was Rp 1,090/kg with a benefit Rp 1,911/kg and an R/C ratio 1.59. The determinant factors for farmers to select soybean for cropping over other crops were: (1) low cost of soybean production; (2) easy marketing and high selling price of soybean, and (3) relatively easy crop cultivation. Other factors to be considered by farmers were: (1) availability of seeds, and (2) the availability of seed support from the government. In the major soybean production areas of East Java and Central Java, farmers grow soybean due to its suitability with the agroecology and the local cropping pattern.